Interdisciplinary approaches to product design, innovation, & branding in international marketing - Swan, K. Scott; Zou, Shaoming (Emerald, 2012)
Interdisciplinary approaches are critical to solve the interesting problems of the day. Branding, product design, and innovation are topics that have not been covered in the series so far but have been gaining attention. In all three cases, there is significant research and practitioner interest. This volume seeks to capture and synthesize the cutting-edge knowledge in the area of branding, product design, innovation, and strategic thought in international marketing. This volume was conceived from a conference held at The College of William & Mary where speakers from many fields - including business, arts, architecture, industrial design, and engineering - were invited to share their methods, findings and insights. The interdisciplinary nature of the conference and this subsequent volume serve to help us gain an appreciation for alternative perspectives while also facilitating cross-disciplinary research in these important areas.
Keywords: Business & Economics -- Marketing -- Industrial.; Business & Economics -- Marketing -- General.; Business & Economics -- Marketing -- Research.; Sales & marketing.; Market research.; Branding (Marketing); Export marketing.; elektronické knihy; electronic books